Numerical modeling on prospective buffer layers for tungsten di-sulfide (WS2) solar cells by scaps-1D - Sobayel K.; Rahman K.S.; Karim M.R.; Aijaz M.O.; Dar M.A.; Shar M.A.; Misran H.; Amin N. (S.C. Virtual Company of Phisics S.R.L, 2023)
In this study, tungsten di-sulphide (WS2), one of the key transition-metal dichalcogenide (TMDC) materials, is used as solar cell absorber material with a suitable solar cell configuration and analyzed by SCAPS-1D. Other main focuses include optimum absorber layer thickness, suitable material for buffer layer instead of CdS and effect of operating temperature on solar cell performance. An efficiency of 19.48% (with Voc of 0.90 V, Jsc of 24.94 mA/cm2 and fill factor of 0.86) has been found for the cell with CdS based buffer layer. High efficiency WS2 solar cells have the optimized absorber thickness in the range of 2 m to 3 m. Moreover, the desired thickness of the buffer layer is observed in between 4060 nm. Among different types (ZnO, ZnSe, ZnS, CdS and In2S3) of buffer layers, ZnO based WS2 solar cell shows the potential to reach out the highest efficiency of 25.71%. However, cell with ZnO buffer layer shows a temperature gradient of-0.24%/K. All these simulation results provide significant hints that may lead to higher efficiency of WS2 solar cells with beneficial experimental studies in practical implementation. 2018, National Institute R and D of Materials Physics. All rights reserved.